2021
DOI: 10.2147/cmar.s289773
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Delayed Chemotherapy on the Decrease of CA125 in Epithelial Ovarian Cancer During Coronavirus Disease Pandemic in 2020

Abstract: Objective: To investigate whether patients with epithelial ovarian cancer were affected by delayed chemotherapy during the coronavirus disease pandemic in 2020. Materials and Methods: A delay of more than 21 days in the planned chemotherapy was defined as "delayed chemotherapy." Forty-five patients with epithelial ovarian, fallopian tube, and peritoneal cancer were delayed between January 1 and March 30, 2020 in the First Affiliated Hospital of Chongqing Medical University. Thirty-two cases were enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Pyeon et al 8 reported that delaying palliative chemotherapy had no adverse effects on the survival of patients with recurrent ovarian cancer. Delayed chemotherapy had no effect on the chemotherapy efficacy and declined levels of cancer antigen (CA) 125 during the coronavirus disease 2019 (COVID-19) pandemic 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Pyeon et al 8 reported that delaying palliative chemotherapy had no adverse effects on the survival of patients with recurrent ovarian cancer. Delayed chemotherapy had no effect on the chemotherapy efficacy and declined levels of cancer antigen (CA) 125 during the coronavirus disease 2019 (COVID-19) pandemic 9 .…”
Section: Introductionmentioning
confidence: 99%